English Language Learning with Flashcard Media and Educational Posters to Improve Language Education - Rani Santika; Rafi Farizki; Hanif Nurcholish Adiantika (Syntax Corporation Indonesia, 2023)
Supporting learning media is an important role in increasing the level of English proficiency students, the teacher is responsible for implementing learning media in teaching process. One of them, in using flashcard and posters. This research is sociolinguistic research that focuses on efforts to improve education through flashcards and educational posters at SDN Haurseah 1 (one). The purpose of this study was to describe the effectiveness of language learning using flashcard media and educational posters and to find out the importance of learning English in an effort to improve language education and improvement in English vocabulary by using interactive and educative learning media. The research method used in this research is classroom action research. The results showed that the media flashcards and educational posters used as media for learning English at SDN Haurseah 1 were effective and had a significant effect on improving language education. So, it can be said that the development of learning media is an effort to improve the quality of education.